Impact of Social Media on Power Relations of Korean Health Activism - KyuJin Shim (Media and Communication, 2014)
This case study explores how the Korea Leukemia Patient Group (KLPG) uses social media in its internal communication strategy and how that empowers its relationship with external counterparts. This study’s findings indicate that the communication strategy of the local health Non-Governmental Organization (NGO) is changing in response to the increased effectiveness and impact of social media. Using social media (e.g., Twitter) the KLPG can quickly and effectively construct an issue-based advocacy group. Consequently, more legitimacy and representativeness through collected support from the general public have further empowered the KLPG. Yet, the sustainability component in the relationships built through social media use was not evidenced in the current findings. The effects of social media use were analyzed based on data from interviews with top-level KLPG executive members and general members, and from documentation and archival materials. Limitations and suggestions for future research are included.